FAILING OF INFORMATION TRANSMISSION BY DORSAL HIPPOCAMPUS DUE TO MICROINJECTION OF COLCHICINE IN RAT’S CORTICAL AREA 1 - Naseri, Afsaneh; Karami, Manizheh; Jalali Nadoushan, Mohammadreza (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: Colchicine has been introduced recently as a neurotoxin with damage effect on neurons of hippocampal cortical area 1 (CA1). Effect of colchicine, a plant derived neurotoxin on memory retrieval was explored experimentally by means of novelty seeking task in intact Wistar rats. Methods: The subjects were cannulated by stereotaxic apparatus at coordinates adjusted for the CA1 area. After recovery, all animals experienced the novelty seeking paradigm using an unbiased conditioning device. First, they were habituated with the conditioned place preference (CPP) apparatus. They were then confined in one part of the CPP box for 3 consecutive days. Finally, the animals were microinjected colchicine (1-25 μg/rat) intra‑hippocampal CA1 prior to testing. Control group was cannulated too, but, solely injected saline (1-μl/rat, intra-CA1). The time spent in the novel part of the device and the motivational signs of the rats were measured. Furthermore, the possible cell injury effect of the toxin on the CA1 layer was verified. Results: The alkaloid caused significant novelty seeking behavior in the experimental animals though did not show a significant effect on the compartment entering. The destruction effect of the neurotoxin on the treated rats' dendrites spines was evidenced. Conclusion: Based on this finding the information transmission by dorsal hippocampal pyramidal cells may impair with an administration of neurotoxin colchicine, intra-CA1. Keywords: Colchicine, Memory retrieval, Novelty seeking behavior, Cortical area 1, Pyramidal cell layer.